Crystal structure and Hirshfeld surface analysis of two organic salts based on 1,3,4-thiadiazole derivatives - Lidiya Izotova; Gulnara Shakirzyanova; Omankul Xolbekov; Shukhrat Turageldiyev; Bahrom Babaev; Bahtiyar Ibragimov (Acta Crystallographica Section E: Crystallographic Communications, 2023)
During attempts to achieve interaction between 2-amino-5-ethyl-1,3,4-thiadiazole with oxalyl chloride and 5-mercapto-3-phenyl-1,3,4-thiadiazol-2-thione with various diacid anhydrides, we obtained two co-crystals (organic salts), namely, 2-amino-5-ethyl-1,3,4-thiadiazol-3-ium hemioxalate, C4H8N3S+·0.5C2O42−, (I), and 4-(dimethylamino)pyridin-1-ium 4-phenyl-5-sulfanylidene-4,5-dihydro-1,3,4-thiadiazole-2-thiolate, C7H11N2+·C8H5N2S3−, (II). Both solids were investigated by single-crystal X-ray diffraction and by Hirshfeld surface analysis. An infinite one-dimensional chain along [100] is generated through O—H...O interactions between the oxalate anion and two 2-amino-5-ethyl-1,3,4-thiadiazol-3-ium cations in compound (I), and a three-dimensional supramolecular framework is generated through C—H...O and π–π interactions. In compound (II), an organic salt is formed by a 4-phenyl-5-sulfanylidene-4,5-dihydro-1,3,4-thiadiazole-2-thiolate anion and a 4-(dimethylamino)pyridin-1-ium cation, which are combined by an N—H...S hydrogen-bonding interaction, forming a zero-dimensional structural unit. As a result of intermolecular π–π interactions, the structural units are combined into a one-dimensional chain running along the a-axis direction.